ORGANIZATIONAL AND ECONOMIC MECHANISM OF INVESTMENT FINANCING OF THE AGRARIAN SECTOR: FINANCE - Babadjanov Abdirashid Musayevich (Bright Mind Publishing, 2025)
The article examines the issues of financing investments in the agrarian sector during the growth period of the economy and its organizational and economic mechanism, and also reveals the problems of their scientific solution. On this basis, appropriate conclusions are formed and practical recommendations are made.
Keywords: Agrarian sector, research, economics, investment, financing, method, mechanism.